Exploring challenges faced by social workers on the management of foster care backlog at the Department of Social Development, Limpopo Province, South Africa - Matsoso, Sisimogang Philadelphia (My University, 2022)
The foster care backlog has been a challenge in the National Department of Social Development for some years which resulted in the lapsing of foster care grants and thousands of children left without legal and statutory protection. Due to this, civil society took the Department of Social Development to court as this challenge impacted negatively on the family functioning of foster families as they lost access to social grants. The Department of Social Development was ordered by the South Gauteng High Court to come up with an extensive legal solution by the end of December 2014 but, to date, the foster care backlog is still piling up and foster families‟ standard of life is threatened. The social workers who are mandated by the Children‟s Act to conduct the statutory process and place children in foster care are inundated by the high foster care backlog. The aim of the research study was to explore the challenges social workers face in relation to managing foster care backlog cases at the Department of Social Development in the Polokwane Municipality area, Limpopo Province. The research study was based on a qualitative research method whereby a small sample of 21 foster care social workers from three service points (Aganang Cluster, Polokwane East and Polokwane West) were interviewed. The researcher used face to face semi-structured interviews to collect primary data from the participants. The findings from the study affirmed that there were indeed challenges in managing the foster care backlog. Lack of support and training, together with inequitable distribution of cases, are the most dominant challenges identified by the participants. In order for the provincial Department of Social Development to reduce the high caseload and for the clients to continue receiving the best service, the research study recommends that the vacant post be filled as soon as possible. Furthermore, training on legislation dealing with children including the Children‟s Act is also recommended for social workers. The researcher is of the opinion that the findings and the recommendations of the study may add value in managing foster care backlog in the Polokwane Municipality area and Limpopo Province as a whole, if they can be considered and applied.
Thesis (M.Dev. (Development Planning and Management)) -- University of Limpopo, 2022
Keywords: Foster care; Social development; Foster care backlog; Social grants; Adoption; Adoption; Social workers -- South Africa -- Limpopo; Foster children -- Care -- South Africa -- Limpopo